2012
DOI: 10.1002/cmdc.201100538
|View full text |Cite
|
Sign up to set email alerts
|

8‐Substituted 3‐Arylcoumarins as Potent and Selective MAO‐B Inhibitors: Synthesis, Pharmacological Evaluation, and Docking Studies

Abstract: Neurodegenerative disorders are becoming more prevalent given the increase in the aging population. This has inspired active research in the development of new drugs that could mark an important advance in the treatment of complex diseases such as Alzheimer's and Parkinson's. With the aim of finding new MAO-B-selective inhibitors, we report the synthesis, in vitro evaluation, and docking simulation of a new series of 3-arylcoumarins variously substituted at the 8-position. Most of the studied compounds show hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…11,12 A few reports on docking study of 3-substituted coumarins may be found in the literature. 13,14 To provide additional insights into the binding mode, molecular docking studies of 3-phenylcoumarins (1-9) (scheme 1) 5,15 were performed in the active site of MAO-B. Given the imperfection of docking simulations in providing the information on intermolecular binding energy components, 16 subsequent to the docking studies, we estimated the participation of each amino acid in total binding energy via an Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 A few reports on docking study of 3-substituted coumarins may be found in the literature. 13,14 To provide additional insights into the binding mode, molecular docking studies of 3-phenylcoumarins (1-9) (scheme 1) 5,15 were performed in the active site of MAO-B. Given the imperfection of docking simulations in providing the information on intermolecular binding energy components, 16 subsequent to the docking studies, we estimated the participation of each amino acid in total binding energy via an Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, variously substituted 3-amidocoumarins are described that exert neuroprotection in vitro against hydrogen peroxide in rat cortical neurons, as well as antioxidant activity in a1 ,1-diphenyl-2-picrylhydrazyl (DPPH·) radicals cavenging assay.S elective and reversible inhibitors of the MAO-B isoform were identified. [14] Coumarins have been found to act as antioxidants and anti-inflammatory agents, [15] neuroprotective agents, [16,17] antidepressants, [18] anticonvulsants, [19] antibacterials, [20] antivirals, [21] anticancera gents, [22,23] anticoagulants, [24] anti-hypertensives, [25] ande nzyme inhibitors, [26][27][28][29][30][31][32][33] amongo ther activities. However,t he compounds describedh erein adhere to Lipinski'sr ule of five, suggesting that this novel scaffold has desirable properties for the development of potential drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly,i nt he case of the 3-benzamidocoumarins, substi-tution at position 4w ith ah ydroxy group abolishes MAO-B activity,but the compoundsr emain active in the neuroprotection model.F urther evaluation of 3-heteroarylamide derivatives indicatest hat it is the nature of the heterocycle that determines the neuroprotective effects.E valuationi naparallela rtificial membrane permeability assay (PAMPA) highlighted the need to furtheri mprovet he blood-brain barrier permeability of this compound class. [27][28][29][30][31][32][33] In recent years, simple coumarins substituted at positions 3o r4have been described to exhibit activity as inhibitors of cholinesterases (ChE), both acetylcholinesterase (AChE)a nd butyrylcholinesterase (BuChE). neuronal degeneration of the dopaminergic nigrostriatalp athway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumarins are also described as antiviral, vasorelaxant, antioxidant, antimicrobial, anticancer, anti-inflammatory and enzymatic inhibitors [22][23][24][25][26][27][28][29][30][31][32][33], but limited data is available concerning their antioxidant activity [22,30,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%